Online Shop and Delivery Services Utilization in Influencing SMEs Development - Syukur, F M; Tawami, T (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This paper aims to assess the extent to which the Integrated Online Shop and Delivery Services system gives impacts on the success of SMEs development. The study is conducted by giving Likert scale questionnaires to 30 restaurants operator across Bojongsoang district in Bandung and applies the expanded Technology Acceptance Model. The data then be analysed using the suggested method for Likert Scale data analysis which involves mean, standard deviation, and correlation analysis. The result indicates that the Integrated Online Shop has positively impacted the successful growth of the restaurants. With the total score of 74%-80% each for the total of 4 variables, they are easy accessibility, online publication, user’s convenience, and support services. Restaurant’s operators agree that the system has helped their restaurant’s development success. It can be concluded that the integrated online shop and delivery services system has helped SMEs to improve their success and growth.